O leitor biblioteca : leitura, recepção e a transformação do leitor em livro literário - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This work proposes, within the literary theory and restricting to the theory of the reader: the library reader. We will use by theorists: Gaston Bachelard (1957), Wolfgang Iser (1976), Umberto Eco (1979), Linda Hutcheon (1980), Roland Barthes (1984), Alberto Manguel (1996a; 2000b; 2004c; 2013d), Regina Zilberman (2000), George Steiner (2003), Rildo Cosson (2006), Tzvetan Todorov (2007) and Maryanne Wolf (2018), to propose the library reader. The thematic axis involves presenting the transformation of the literature reader into a literary book. This metamorphosis takes place in the sense that the reader is so crossed by solitude and the pleasure of reading that, by sharing his readings, he himself becomes narratives. Thus, our theme is not the erudite reader or similar, we intend to demonstrate that the purpose of reading is not reading itself, but the reader becoming a living medium in which other readers have access. Such a transformation is anchored in the aesthetics of reception, the aesthetics of effect and the theory of metafiction. Thinking about the receptions and the effects that the readings promote in the contemporary reader, we want to present a poetics not yet contemplated in the Theory of Literature: the poetics of sharing.
The library reader: reading, reception and the transformation of the reader into a literary book
Keywords: Leitor. Borges; Leitura; Poética do compartilhamento; Fahrenheit 451; Borges; Leitorbiblioteca; Reader; Reading; Poetics of sharing; Libraryreader; LINGUISTICA, LETRAS E ARTES